Characterization of fluorescent synthetic epicocconone-based dye through advanced light microscopies for live cell imaging applications. (June 2017) - Schapman, Damien; Perraudeau, Caroline; Bénard, Magalie; Gallavardin, Thibault; Boulangé, Agathe; Leleu, Stéphane; Lebon, Alexis; Franck, Xavier; Galas, Ludovic
Abstract: Identification of new fluorescent biomarkers is a key issue to decipher mechanisms in living cells. Isolated from the fungus Epicoccum nigrum, natural epicocconone (NE) establishes a covalent and reversible link with primary amines and has been identified as a new fluorescent dye for cell imaging. In the present study, the properties of a synthetic and multifunctional analogue of epicocconone (SE) have been compared to those of NE through 1-photon (1P) and 2-photon (2P) advanced light microscopies. 1P Λλ confocal microscopy analyses revealed that, in cell culture medium, SE and NE displayed two peaks of excitation (ex) at 480 and 530 nm and a large band of emission (em) with a maximum at 610 nm. In living cells, SE presented sharper bands compared to NE with maxima at 545 nm (ex) and 605 nm (em). In 2P microscopy, SE and NE presented maxima around 790 nm (ex) and 595 nm (em) when diluted in cell culture medium. In living cells, SE did not present any large disturbing blue-shift for emission that was observed for NE. In addition, 2P bands for SE were sharper than the NE ones. SE was 2–3 times more fluorescent than NE as determined through 1P and 2P approaches. SE did not induce any cytotoxicity and was adapted for time-lapse acquisition. In PC12 cells, SE broadly labeled nuclear and plasma membranes, vesicles-like structures and organelles including the Golgi apparatus and mitochondria. Taken together, these data indicate that SE has appropriate properties for in vitro and in vivo cell biology studies and presents many advantages compared to NE for 1P and 2P microscopies. Highlights: SE is a fluorescent synthetic and multifunctional analogue of epicocconone. Properties of SE in living cells: Ex 545 nm/Em 605 nm for 1-photon microscopy (1P). Properties of SE in living cells: Ex 774 nm/Em 592 nm for 2-photon microscopy (2P). SE is 2–3 times more fluorescent than the natural epicocconone. SE presents many advantages compared to the natural form for both 1P and 2P.